Comparative evaluation of the microbial diversity and metabolite profiles of Japanese-style and Cantonese-style soy sauce fermentation - Tan, Guiliang; Wang, Yi; Hu, Min; Li, Xueyan; Li, Xiangli; Pan, Ziqiang; Li, Mei; Li, Lin; Zheng, Ziyi (Frontiers in Microbiology, 2022)
Microorganisms play essential roles in flavor formation during soy sauce fermentation. Different soy sauce fermentation types significantly affect flavor formation. However, comparisons of microbial communities and metabolites between different fermentation types have been little studied. Here, we investigated variation in microbial communities, metabolite profiles, and metabolic pathways during Japanese-type (JP) and Cantonese-type (CP) fermentation. Free amino acids and volatile compound profiles varied significantly between fermentation types, with JP samples containing higher contents of esters (39.84%), alcohols (44.70%) (p < 0.05) in the 120 d fermentation samples. Volatile compound profiles varied significantly between fermentation types, with JP samples containing higher contents of esters, alcohols, and free amino acids (p < 0.05). Metagenomic analysis indicated that both JP and CP communities were dominated by Tetragenococcus, Staphylococcus, Weissella (bacteria), and Aspergillus (fungi), but the two communities varied differently over time. Tetragenococcus drastically increased in abundance throughout the fermentation (from 0.02% to 59.2%) in JP fermentation, whereas Tetragenococcus (36.7%) and Staphylococcus (29.7%) dominated at 120 d of fermentation in CP fermentation. Metagenomic functional profiles revealed that the abundances of most genes involved with carbohydrate, amino acid, and lipid metabolism exhibited significant differences between fermentation types (p < 0.05) during the middle to late fermentation stages. Furthermore, predicted metabolic pathways for volatile substance biosynthesis differed between JP and CP fermentation, likely explaining the differences in flavor metabolite profiles. In addition, most of the genes associated with flavor generation were affiliated with Tetragenococcus, Weissella, Staphylococcus, Bacillus, and Aspergillus, suggesting that these microbes play important roles in flavor production during soy sauce fermentation. This study significantly improves our understanding of microbial functions and their metabolic roles in flavor formation during different soy sauce fermentation processes.